Decreased expression of A20 is associated with ocular Behcet's disease (BD) but not with Vogt-Koyanagi-Harada (VKH) disease. Issue 8 (26th April 2018) - He, Yue; Wang, Chaokui; Su, Guannan; Deng, Bolin; Ye, Zi; Huang, Yang; Yuan, Gangxiang; Kijlstra, Aize; Li, Hong; Yang, Peizeng
Abstract : Purpose: A20 is a ubiquitously expressed and inducible cytosolic protein, which plays an important role in the negative regulation of inflammation and immunity. In this study, we investigated the role of A20 in Behcet's disease (BD) and Vogt-Koyanagi-Harada (VKH) disease. Methods: The levels of A20 in peripheral blood mononuclear cells (PBMCs) and dendritic cells (DCs) were detected in BD patients with active and inactive uveitis, VKH patients with active and inactive uveitis, and normal subjects, respectively, by real-time PCR. The effect of A20 silencing was performed by transduction of DCs with adenovirus containing an A20 shRNA vector. The effect of A20 silencing on the maturation of DCs was measured by flow cytometry. The effect of A20 silencing of DCs on cytokine production by DCs and CD4 + T cells was analysed by ELISA. The phosphorylation levels of JNK, p38 and ERK1/2 were detected by flow cytometry. Results: The expression of A20 was markedly decreased in PBMCs and DCs obtained from BD patients with active uveitis, but not in patients with VKH disease as compared with normal controls. Silencing of A20 significantly increased the levels of interleukin (IL)-1β and IL-6 and suppressed the expression of the anti-inflammatory cytokines IL-10 and IL-27. Downregulation of A20 also led to an increase in IL-17 production by CD4 + T cells. However, downregulation of A20 in DCs did not have an effect on cell surface markers such as CD40, CD80, CD83, CD86 and HLA-DR. Silencing of A20 caused an increased expression of phospho-JNK and phospho-MAPK p38 but not phospho-ERK1/2. Conclusions: This study showed that the expression of A20 was decreased in BD patients with active uveitis but not in VKH disease. Decreased expression of A20 may lead to an enhanced activation of proinflammatory Th17 cells, causing a reactivation of BD.